1993
DOI: 10.1002/aja.1001970203
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of CD9 in the developing and mature rat nervous system

Abstract: CD9 is a cell surface protein implicated in intercellular signaling that has been identified in selected cell types of the hematopoietic system. To begin a study of the role of CD9 in the developing and adult nervous system, we used the anti-rat CD9 monoclonal antibody ROCAB to determine the distribution of this protein. The identity of the antigen in these tissues was confirmed by immunoblotting and peptide sequencing. Early embryonic sympathetic and dorsal root ganglion sensory neurons and adrenal chromaffin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 36 publications
5
48
2
Order By: Relevance
“…They are thus supposed to be "adapters for membrane proteins" or "molecular facilitators" that mediate the formation of large molecular complexes and allow them to function more efficiently. CD9 is one of the best characterized TM4SF members, and a number of studies have suggested that CD9 is involved in cell signaling (21,22), cell growth (6), cell motility (23,24), cell adhesion (25)(26)(27), tumor cell metastasis (28 -30), and development and maintenance of neural system (31)(32)(33)(34). However, despite such fundamental roles, evidence to demonstrate the role of CD9 in molecular complexes is limited.…”
Section: Hb-egf/tgf-␣ Chimericmentioning
confidence: 99%
“…They are thus supposed to be "adapters for membrane proteins" or "molecular facilitators" that mediate the formation of large molecular complexes and allow them to function more efficiently. CD9 is one of the best characterized TM4SF members, and a number of studies have suggested that CD9 is involved in cell signaling (21,22), cell growth (6), cell motility (23,24), cell adhesion (25)(26)(27), tumor cell metastasis (28 -30), and development and maintenance of neural system (31)(32)(33)(34). However, despite such fundamental roles, evidence to demonstrate the role of CD9 in molecular complexes is limited.…”
Section: Hb-egf/tgf-␣ Chimericmentioning
confidence: 99%
“…One of these proteins, CD9, has been recently described in the rat nervous system (Tole and Patterson, 1993;Kaprielian et al, 1995). CD9 interacts in cis (within the membrane of the same cell) with members of the integrin protein family in many cell types, and many of the functions ascribed to CD9 may depend on CD9 -integrin interactions (Higashihara et al, 1985;Slupsky et al, 1989;Letarte et al, 1992;Rubinstein et al, 1994;Nakamura et al, 1995;Shaw et al, 1995).…”
Section: Abstract: Cd9; Tetraspan Proteins; Antibody Perturbation; Nmentioning
confidence: 99%
“…CD9 is also expressed by neurons (Tole and Patterson, 1993;Kaprielian et al, 1995). Although CD9 is not detectable on migrating neural crest cells, expression is upregulated very soon after these cells coalesce into various tissue derivatives (E11-E12 in the rat), and CD9 is found on the surface of neuroblasts in the SCG at E12 and in DRG at E15.…”
Section: Abstract: Cd9; Tetraspan Proteins; Antibody Perturbation; Nmentioning
confidence: 99%
“…Increasing evidence suggests that this protein is involved in a variety of functions, such as cell signaling (Tai et al, 1996;Griffith et al, 1991), cell growth , cell motility (Shaw et al, 1995;Schmidt et al, 1996), cell adhesion Anton et al, 1995;Masellis-Smith and Shaw, 1994), tumor cell metastasis (Ikeyama et al, 1993;Miyake et al, 1991;Si and Hersey, 1993), muscle cell formation (Tachibana and Hemler, 1999), development and maintenance of the neural system (Kaprielian et al, 1995;Tole and Patterson, 1993;Nakamura et al, 1996;Kagawa et al, 1997), sperm-egg fusion (Miyado et al, 2000;Le Naour et al, 2000;Kaji et al, 2000) and viral infections (Loffler et al, 1997;Schmid et al, 2000). CD9 forms complexes with a number of membrane proteins which include integrin =3>1 (Nakamura et al, 1995), =6>1 (Berditchevski et al, 1996;Hadjiargyrou et al, 1996), the neural adhesion molecule L1 (Schmidt et al, 1996), CD46 (Lozahic et al, 2000), the membrane-anchored form of heparin-binding EGF-like growth factor (proHB-EGF) (Iwamoto et al, 1994) and other members of the tetraspanins .…”
mentioning
confidence: 99%